THE ASSET-BASED COMMUNITY DEVELOPMENT (ABCD) DENGAN ANALISIS RASCH: PEMBELAJARAN AGAMA ISLAM RESPONSIF GENDER - Indah Wigati (Tadrib: Jurnal Pendidikan Agama Islam, 2021)
Salah Nama Island is located in RT 01, Mariana Ilir sub-district, Banyuasin Regency, South Sumatra. The livelihoods of the people on this island are fishermen and farmers. The activity of earning a living results in a lack of public attention to religious knowledge. In addition, on this island there are elderly people who do not have the ability to read and write, so the delivery of information about religious knowledge requires special attention. The focus of the assistance is how to increase knowledge and patterns of Islamic religious learning about gender responsive prayer and taharah for the poor people of Salah Nama Island.This assistance aims to determine efforts to increase knowledge and analyze effective gender-responsive Islamic religious learning patterns for the people of Salah Nama Island. This mentoring uses the ABCD approach and andragogy learning patterns. Data were analyzed qualitatively, rasch, and gender.The results showed that the efforts used to increase religious knowledge were discussions, determining the focus of mentoring, facilitating resource persons, goals and objectives of mentoring, and mentoring outputs. The pattern of gender-responsive Islamic religious learning is carried out by mapping assets, raising the spirit of improvement, asset management, and changing actions and gender roles in Islamic religious learning. Rasch's analysis shows that the results of religious understanding before and after mentoring have increased. This shows that there is an increase in religious understanding and worship practices in accordance with Islamic law.